2017
DOI: 10.2147/ijn.s132369
|View full text |Cite
|
Sign up to set email alerts
|

Selection of potential iron oxide nanoparticles for breast cancer treatment based on in vitro cytotoxicity and cellular uptake

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) are promising tools for the treatment of different diseases. Their magnetic properties enable therapies involving magnetic drug targeting (MDT), hyperthermia or imaging. Depending on the intended treatment, specific characteristics of SPIONs are required. While particles used for imaging should circulate for extended periods of time in the vascular system, SPIONs intended for MDT or hyperthermia should be accumulated in the target area to come into close prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 47 publications
2
50
0
1
Order By: Relevance
“…ICP-OES demonstrated that an average of 12.8 ± 3.6 pg Fe was internalised into each cell (with 12.8 pg Fe equating to 16,487 nanoparticles) and subsequent Prussian blue staining confirmed this internalisation and identified the nanoparticles propensity to accumulate around the nuclear membrane. This level of iron uptake into cells is comparable to the results reported from similar protocols published previously [35][36][37]. Next, intracellular hyperthermia, extracellular hyperthermia, and intracellular and extracellular hyperthermia were compared to define differences in viability through Annexin V/7-AAD staining.…”
Section: Discussionsupporting
confidence: 83%
“…ICP-OES demonstrated that an average of 12.8 ± 3.6 pg Fe was internalised into each cell (with 12.8 pg Fe equating to 16,487 nanoparticles) and subsequent Prussian blue staining confirmed this internalisation and identified the nanoparticles propensity to accumulate around the nuclear membrane. This level of iron uptake into cells is comparable to the results reported from similar protocols published previously [35][36][37]. Next, intracellular hyperthermia, extracellular hyperthermia, and intracellular and extracellular hyperthermia were compared to define differences in viability through Annexin V/7-AAD staining.…”
Section: Discussionsupporting
confidence: 83%
“…This is the case of Bovine Serum Albumin (BSA) protein [ 16 ]. The same authors from Reference [ 16 ] are working today on human serum albumin, for better biocompatibility, thus supporting the crucial role that protein corona can play [ 17 ].…”
Section: Introductionmentioning
confidence: 98%
“…Bidkar, Sanpui, and Ghosh () have used PI to confirm viable/apoptotic cells in paclitaxel‐loaded selenium nanoparticles treated colon (HT29), lung (A549), cervical (HeLa) and breast (MCF7) cancer cells. Poller et al () have shown viable/dead breast cancer cells (BT‐474, MCF7, MDA‐MB‐231 and T‐47D) treated with lauric acid‐coated iron oxide nanoparticles using PI. 7‐Aminoactinomycin D is a fluorescent dye that can also be used to detect viable/non‐viable cells (excluded by viable cells) by fluorescence microscopy and FCM (Zembruski, Stache, Haefeli, & Weiss, (Figure ).…”
Section: Cell Viability/cytotoxicity and Antiproliferative Assaysmentioning
confidence: 99%